A reevaluation of erythroid predominance in Acute Myeloid Leukemia using the updated WHO 2016 Criteria. (June 2018) - Margolskee, Elizabeth; Mikita, Geoff; Rea, Bryan; Bagg, Adam; Zuo, Zhuang; Sun, Yi; Goswami, Maitrayee; Wang, Sa; Oak, Jean; Arber, Daniel; Allen, M.; George, Tracy; et al.
Abstract The 2016 WHO update changed the diagnostic criteria for myeloid neoplasms with erythroid predominance, limiting the diagnosis of acute myeloid leukemia to cases with ≥20% blasts in the bone marrow or peripheral blood. Although acute myeloid leukemia with ≥50% erythroid cells has historically been presumed to represent acute myeloid leukemia with myelodysplasia-related changes, this hypothesis has never been systematically examined. We sought to investigate the clinicopathologic, cytogenetic, and molecular features of acute myeloid leukemia with erythroid predominance to subclassify cases as defined by the 2016 WHO. We retrospectively identified patients with ≥50% erythroid precursors and either ≥20% bone marrow blasts or ≥20% peripheral blood blasts at the time of initial diagnosis at seven major academic centers. Laboratory and clinical data were obtained. Patients were then reclassified according to 2016 WHO guidelines. A matched control group was also obtained. We identified 146 patients with acute myeloid leukemia with erythroid predominance (62% M, average age: 62 y, range: 5–93 y). Of these, 91 were acute myeloid leukemia with myelodysplasia-related changes, 20 (14%) were therapy-related myeloid neoplasm, 23 (16%) acute myeloid leukemia, not otherwise specified, and ten acute myeloid leukemia with recurrent cytogenetic/molecular abnormalities. The bone marrow blast count ranged from 9–41%. There was no difference in survival for patients with erythroid predominance compared to patients with acute myeloid leukemia without erythroid proliferations. In a multivariable analysis, cytogenetic risk was the only significant predictor of survival. We find a significantly lower rate ofFLT3 andRAS pathway alterations in acute myeloid leukemia with erythroid predominance compared to controls. Our study is one of the first to apply the 2016 WHO guidelines for classification of acute myeloid leukemia. We find acute myeloid leukemia with erythroid predominance is a heterogeneous group and that erythroid richness has no impact on overall survival.